Pengaruh Leverage dan Profitabilitas terhadap Manajamen Laba pada Perusahaan Sub Sektor Konstruksi Bangunan yang Terdaftar di BEI Tahun 2020-2024 - Rahadathul Aisy; Syahrial Addin; Yulia Mujiaty (Jurnal Publikasi Ilmu Manajemen, 2025)
Along with the strengthening intensity of globalization in the global economic landscape, companies from various parts of the world are required to maintain stable market share. This condition encourages increasingly competitive competition between some of important sectors, including the building construction sub-sector. With the need for the construction of buildings and public facilities always high, each company seeks to display optimal financial performance to attract investor’s attention. Consequently, a lot of businesses use earnings management techniques to preserve their positive public perception. This study aims to empirically examine the effect of leverage and profitability on earnings management in building construction sub-sector companies listed on the IDX in 2020-2024. The sample consisted of 9 companies that met the criteria using purposive sampling method. Earnings management is measured using the Modified Jones model, leverage is measured by Debt To Equity Ratio, while profitability is measured by Return On Assets. The analysis method used is quantitative and multiple linear regression analysis. The results showed that partially leverage has no significant effect on earnings management, but profitability has a positive and significant effect on earnings management. Simultaneously, leverage and profitability have a significant effect on earnings management.